2011
DOI: 10.1007/s11104-011-0779-x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of heme oxygenase-1 with β-CD-hemin complex mitigates cadmium-induced oxidative damage in the roots of Medicago sativa

Abstract: Using pharmacological and biochemical approaches, the functional roles of heme oxygenase-1 (HO-1) induction in cadmium (Cd)-stressed alfalfa (Medicago sativa) seedling roots caused by a metalorganic complex (β-cyclodextrin-hemin, β-CDhemin, CDH) and the well-known HO-1 inducer hemin, were investigated and compared. Cd-stressed seedling roots exhibited severe oxidative damage, whereas up-regulation of HO-1 by CDH and hemin pretreatment prevented this toxic response, as evidenced by the decrease of lipid peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…6c), were consistent with previous results in rice (Chao et al 2010) and alfalfa seedlings (Fu et al 2011), although the opposite effect was observed in pea plants subjected to higher doses of Cd treatment (Hana et al 2008). Different responses of APX and POD were also discovered in maize leaf (Krantev et al 2008), suggesting that the induction or suppression of antioxidant enzyme activities in heavy metal-stressed plants might be dependent on the concentration of heavy metals and exposure times, and even different plant species (Sharma and Dietz 2009).…”
Section: H 2 S and No Alleviate CD Toxicitysupporting
confidence: 91%
“…6c), were consistent with previous results in rice (Chao et al 2010) and alfalfa seedlings (Fu et al 2011), although the opposite effect was observed in pea plants subjected to higher doses of Cd treatment (Hana et al 2008). Different responses of APX and POD were also discovered in maize leaf (Krantev et al 2008), suggesting that the induction or suppression of antioxidant enzyme activities in heavy metal-stressed plants might be dependent on the concentration of heavy metals and exposure times, and even different plant species (Sharma and Dietz 2009).…”
Section: H 2 S and No Alleviate CD Toxicitysupporting
confidence: 91%
“…1 extends our former results, and shows that after the IAA depletion treatment for 2 d, concentrations between 1 and 100 M hemin significantly induced adventitious root numbers (P < 0.05 or 0.01), with a maximal response at 10 M hemin. These effective concentrations are comparable to those of hemin applied in Medicago sativa (Fu et al, 2011) and Arabidopsis seedlings . The analogous result was also confirmed by the administration of hematin in auxin-depleted cucumber explants (Xuan et al, 2008), although the concentrations of the applied hemin or hematin were approximately hundred-fold higher than the physiological contents of heme in various plant and animal tissues as well as microorganism (Brenner and Bloomer, 1977;Lamba and Webster, 1980;Thomas and Weinstein, 1990;Wang et al, 2005).…”
Section: Effects Of Hemin On Adventitious Rooting and Endogenous No Pmentioning
confidence: 55%
“…Application of Hm or hematin could induce HO activity and HO1 mRNA and HO1 protein expression in cucumber (Xuan et al 2008), Arabidopsis (Xie et al 2011), alfalfa (Fu et al 2011), and tomato roots ). Here, we confirmed that Hm increased HO activity and OsHO1 transcript levels in rice roots.…”
Section: Discussionmentioning
confidence: 98%
“…However, the role of HO regulating LR formation in rice has not been examined. Hemin (Hm), a heme (ferroprotoporphyrin IX) compound, is a potent HO1 inducer (Zilli et al 2008;Fu et al 2011). In this study, we examined the role of HO regulating LR formation in rice, with the effect of Hm on LR formation used as a positive control.…”
Section: Introductionmentioning
confidence: 99%